A Comparative Study of Burnout among Civil Servants and State-Owned Enterprise Employees in the Coastal Regions of North Maluku - Nur Fathin Attiyah; Abdul Hamid (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to investigate the comparative differences in burnout levels between Civil Servants and State-Owned Enterprise (SOE) employees in the coastal regions of North Maluku. A quantitative approach with a cross-sectional design was employed. The sample consisted of 120 respondents (60 civil servants and 60 SOE employees) selected via purposive sampling. Data were collected using a modified 28-item Maslach Burnout Inventory (MBI) scale that demonstrated validity (Pearson Product Moment) range of Item–Total Correlations ranging from 0.238 to 0.854 (criterion r-table = 0.232) and excellent internal consistency (Cronbach alpha = 0.952). Due to the non-normal distribution of the data, non-parametric analyses were performed. Descriptive results indicated that all respondents experienced low (65.8%) to moderate (34.2%) levels of burnout, with zero prevalence of high burnout. The Mann-Whitney U test revealed no significant difference in burnout between civil servants and SOE employees (U = 1592.5, z = -1.090, p = 0.276, effect size r = 0.0995). Furthermore, the Kruskal-Wallis test demonstrated no significant differences in burnout across the healthcare, finance, and public works sectors (χ²= 5.832, df = 2, p = 0.054, effect-size = 0.0327). These findings imply that neither employment status nor work sector directly determines burnout variations in this specific geographic context, suggesting the presence of overriding macro-environmental or socio-cultural buffers in coastal areas.